Applying user signatures on fraud detection in telecommunications networks - Lopes, João (2011)
Fraud in telecommunications is increasing dramatically with the expansion of modern technology, resulting in the loss of billions of dol- lars worldwide each year. Although prevention technologies are the best way to reduce fraud,. Fraudsters are adaptive, searching systematically for new ways to commit fraud and, in most of the cases, will usually find some way to circumvent companies prevention measures. In this paper we expose some of the ways in which fraud is being used against organi- zations, evaluating the limitations of existing strategies and methods to detect and prevent it in todays telecommunications companies. Addition- ally, we expose a data mining profiling technique based on signatures that was developed for a real mobile telecommunications network operator and integrated into one of its Fraud Management Systems (FMS), currently under operation.